Design of an Automatic Slat Conveyor Prototype Based on PLC - Pangaribowo, Triyanto; Mahdy, Evan (SHM Publisher, 2024)
The transfer of goods, commonly known as pick and place, which still relies on manual labor, poses challenges for industrial production companies. In automotive quality inspection, the manual transfer of vehicles by drivers between inspection stations often leads to inefficiencies and missed production targets. This research aims to implement an automated slat conveyor system controlled by PLC to optimize vehicle quality inspection. With this system, vehicles are moved automatically between stations, allowing inspections to be conducted during transit. The automation aligns with the Kaizen philosophy, emphasizing continuous improvement in production processes. The results of testing the slat conveyor automation system indicate that the system successfully achieves a maximum response time of 0.8 seconds, with a speed of 0.6 meters per second.